ETIKA DAN KEPATUHAN HUKUM DALAM PRAKTIK PEMBIAYAAN SYARIAH DI ERA FINTECH - M. Ilham; Nurhayati; Muhammad Albahi; Kiki Hardiansyah Siregar (ITB AAS INDONESIA Surakarta, 2025)
Abstract The development of financial technology (fintech) has brought significant transformation to the global financial system, including Islamic financing. Digital innovation creates major opportunities to expand access to Sharia-based financial services while also presenting new challenges regarding ethics, legal compliance, and adherence to Islamic principles. This study aims to analyze the relationship between ethics, legal compliance, and the implementation of Sharia principles in fintech-based financing practices in Indonesia. Using a qualitative-descriptive approach within a normative-empirical framework, the research examines regulations issued by the Financial Services Authority (OJK), fatwas of the National Sharia Council–Indonesian Ulema Council (DSN-MUI), and relevant literature on Islamic economics and law. The findings indicate that the integration between ethics and law in Islamic fintech still faces challenges such as regulatory and supervisory gaps. Therefore, an integrated compliance governance framework and the application of maqāṣid al-syarī‘ah principles are needed as the foundation for technological design, ensuring that fintech innovation is not only efficient and legally compliant but also just, ethical, and sustainable. Keywords: Islamic fintech, ethics, legal compliance, maqāṣid al-syarī‘ah